COUNSELORS' UNDERSTANDING OF HUMAN NATURE AS AN ORIENTATION FOR COUNSELING PRACTICE - Larasati, Sectio Putri; Nirwana, Herman; Marjohan, Marjohan (LP2M IAI Al-Khairat Pamekasan, 2025)
Human beings are the most noble creatures created by God and have a uniqueness that distinguishes between one individual and another. This uniqueness is a distinctive distinguishing feature between each individual, both psychologically and physiologically. The most basic thing for counselors to understand the individual as the orientation of counseling practice is whether or not the needs of the individual are met because the problems that arise in an individual are not met by their basic needs such as physical, technical, social, taste, and the needs of faith and piety. This will encourage individuals to be in disturbed daily effective life behaviors. Thus, a counselor must try to analyze the condition of the individual as a counseling practice, namely whether or not these five basic needs are fulfilled to be able to provide intervention or assistance to clients when providing counseling services so that they are ineffective daily living conditions.